Smokeless Tobacco (Shamma) and Oral Squamous Cell Carcinoma in Women , 3 Years Retrospective Study , Abu Arish General Hospital - Makrami, eham Mohammed; Mathkur, Mona Yahya Abdullah; Makrami, Ali Mohammed (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Smokeless tobacco, particularly Shamma, also known as Yemeni snuff, is frequently used as a chewing material in Yemen and some parts of South region of Kingdom of Saudi Arabia, is a recognized risk factor for squamous cell carcinoma of the oral cavity. This conclusion based on epidemiologic studies of oral cancer in women, in Yemen cases and some parts of South region of Kingdom of Saudi Arabia. Where the oral cancer death rate in females has been high.The research focus on studies of women led to the identification of the hazards from Shamma use. Preliminary clinical observations indicated that long-term users of Shamma may develop oral cancer. More researches should be stressed on understanding new trends in oral cancer high mortality rates among women.